2010
DOI: 10.4204/eptcs.39.5
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Real Vector Automata

Abstract: This thesis introduces a new data structure, the Implicit Real Vector Automaton (IRVA), suited for representing symbolically polyhedra, i.e., regions of n-dimensional space defined by finite Boolean combinations of linear inequalities. IRVA can represent exactly arbitrary convex and non-convex polyhedra, including features such as open and closed boundaries, unconnected parts, and non-manifold components. In addition, they provide efficient procedures for deciding whether a point belongs to a given polyhedron,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Finite-state representations are not a panacea; however, since the size of NDD and RVA recognising linear constraints can grow linearly with the magnitude of their coe cients, the representations can become unnecessarily large. A possible solution to this problem, consisting of representing some internal structures of automata by algebraic means, is being investigated, see [11] and [17]. Another problem is that the presence of dual encodings is also a source of ine ciency.…”
Section: Discussionmentioning
confidence: 99%
“…Finite-state representations are not a panacea; however, since the size of NDD and RVA recognising linear constraints can grow linearly with the magnitude of their coe cients, the representations can become unnecessarily large. A possible solution to this problem, consisting of representing some internal structures of automata by algebraic means, is being investigated, see [11] and [17]. Another problem is that the presence of dual encodings is also a source of ine ciency.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the SCC of A are related to the polyhedral components of Π [4,3,7]. This can intuitively be explained as follows.…”
Section: Point Decision In Rvamentioning
confidence: 99%
“…Second, in the particular case where one has dim(VS (s )) = dim(VS (s)) + 1, it is essential to ensure that the state s does not represent a boundary of the polyhedral component associated to s. This is done by checking that, among the words w such that s w → s , at least two of them have leading symbols −(i) and +(i) with an identical face number and opposite polarities. This tricky particular case was overlooked in [3].…”
Section: Minimization Algorithmmentioning
confidence: 99%
See 1 more Smart Citation